Synthesis, characterization, and three-dimensional structure generation of zinc oxide-based nanomedicine for biomedical applications - Jin, Su Eon; Jin, Hyo Eon (Pharmaceutics, 2019)
Zinc oxide (ZnO) nanoparticles have been studied as metal-based drugs that may be used for biomedical applications due to the fact of their biocompatibility. Their physicochemical properties, which depend on synthesis techniques involving physical, chemical, biological, and microfluidic reactor methods affect biological activity in vitro and in vivo. Advanced tool-based physicochemical characterization is required to identify the biological and toxicological effects of ZnO nanoparticles. These nanoparticles have variable morphologies and can be molded into three-dimensional structures to enhance their performance. Zinc oxide nanoparticles have shown therapeutic activity against cancer, diabetes, microbial infection, and inflammation. They have also shown the potential to aid in wound healing and can be used for imaging tools and sensors. In this review, we discuss the synthesis techniques, physicochemical characteristics, evaluation tools, techniques used to generate three-dimensional structures, and the various biomedical applications of ZnO nanoparticles.
Keywords: Biomedical application; Physicochemical characteristics; Synthesis; Three-dimensional structure; Zinc oxide nanoparticles